Respiratory manifestations in inherited metabolic diseases: 6‐year single‐center experience. Issue 8 (21st May 2019) - Ilarslan, Nisa Eda Çullas; Gunay, Fatih; Cobanoglu, Nazan; Karaman, Merve; Eminoglu, Fatma Tuba
Abstract: Objectives: We aimed to call attention to respiratory system manifestations which occur in the course of many inherited metabolic diseases (IMD), and present as the leading cause of death. Materials and Methods: We retrospectively reviewed the diagnosis, treatment, and outcome of patients evaluated at our hospital between June 2012 and June 2018 with a diagnosis of IMD and accompanying respiratory manifestations. Results: A total of 50 children (29 [58%] male, 21 [42%] female) with IMD and respiratory manifestations were defined. Disorders of intracellular metabolism (n = 33, 66%) formed the majority, followed by intoxication type metabolic disorders (n = 9, 18%) and energy metabolism disorders (n = 8, 16%). The most frequent respiratory symptoms were snoring (20, 40%), tachypnea (16, 32%) and wheezing (14, 28%). Physical examination findings were signs of respiratory distress (n = 28, 56%), crackles (n = 24, 48%), thoracic deformity (n = 23, 46%), decreased breath sounds (n = 17, 34%), rhonchus (n = 17, 34%), wheezing (n = 17, 34%) and stridor (n = 10, 20%). Major respiratory manifestations were chronic airway aspiration (n = 23, 46%), upper airway obstruction (n = 23, 46%), and recurrent pneumonia (n = 18, 36%). Twenty‐three 23 patients (46%) experienced endotracheal intubation, 9 patients (18%) required whole‐house mechanical ventilation and tonsilloadenoidectomy was performed in 7 patients (14%). Overall survival rate was 70% (n = 35) in a median follow‐up period of 2.36 (0.05‐5.86) years. Conclusions: Respiratory system manifestations of IMD strongly relate with increased morbidity and mortality. Therefore, prompt diagnosis and correct intervention of respiratory complications with a multidisciplinary team including pediatric metabolic diseases specialists, pulmonologists, otorhinolaryngologists, physiotherapists, and anesthesiologists are crucial to prevent progression and irreversible damage.